Differences in Minimum Inhibitory Concentrations of Probiotics and Prebiotics on Staphylococcus aureus - Yuliastuti, Wiwid; Hermawati, Anyanita Hanif; Islamy, Aesthetica (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Currently, the use of antibiotics has increased sharply and use in the long term will have a bad impact on health. So the emergence of efforts in the form of making natural antibiotics by utilizing materials that are easily available in the environment. One of them is milk, where milk is a food product produced by farm animals, for example cows. This milk can be used as a probiotic. This probiotic is made by adding a bacterium and the bacterium that is often used is Lactobacillus casei. In addition to milk, the material that can be used is telang flower, which is one of the typical plants of Ternate, Maluku with purple, white, pink, and blue petals. Telang flower is often used as a traditional medicine because it has many benefits and content in it. Therefore, in this study Telang flower was used as a prebiotic tested on Staphylococcus aureus bacteria. The study was carried out in vitro by the method of laboratory experiments. The design used is Post Test control group only. The test is repeated at each concentration 3 times to obtain accurate results. The inhibition zone is measured using a caliper. The result of the inhibition zone formed from 3 repetitions is taken as the average value. The test results of the minimum inhibitory concentration of probiotics against Staphylococcus aureus bacteria showed results if at a concentration of 1.25% can form an inhibitory zone of 9.47 mm. While the minimum inhibitory concentration test on prebiotics against Staphylococcus aureus bacteria showed results at a concentration of 2.5% can form an inhibitory zone of 9.02 mm. This suggests that probitiks and prebiotics can be used as antibacterials, since at the lowest concentrations used they can form an inhibitory zone. So the higher the concentration of probiotics and prebiotics used, the inhibition zone formed will be greater.